The impacts of knowledge, attitude, awareness and organizational commitment on risk management effectiveness in laboratories - Zuraida Kamaruddin; Zaidi Isa (Penerbit Universiti Kebangsaan Malaysia, 2023)
Whether medical, chemical, or nuclear, the laboratory presents inherent risks, which are further amplified by lab equipment usage. Ensuring laboratory safety in universities and research institutions is thus critical. Based on the knowledge, attitude, and practice model, this study examines how student knowledge, attitude, awareness, and organizational commitment impact the effectiveness of laboratory and workshop risk management. Survey data was collected from 251 engineering students from four southern Malaysian polytechnics and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings reveal that knowledge, awareness, and organizational commitment significantly enhance risk management effectiveness, while attitude has noeffect. These results emphasize the need for institutions to improve students' risk management knowledge and awareness to fortify safety measures and risk management strategies against hazards on campus or in the community